1244. Assessment of the In Vivo Activity of Human-Simulated Exposure of WCK 4282 (High Dose Cefepime [FEP]-Tazobactam [TZB]) against Enterobacterales (EB) and Pseudomonas aeruginosa (PA) in the Neutropenic Murine Thigh Infection Model - Gill, Christian M (Open Forum Infect Dis, 2020)
BACKGROUND: Carbapenems are often used for infections due to extended-spectrum-β-lactamase (ESBL) and cephalosporinase (CSase)-producers. As increased carbapenem utilization is associated with the development of carbapenem resistance, antimicrobial stewardship has targeted non-carbapenem options. WCK 4282 (FEP 2 g-TZB 2 g) offers pharmacodynamically optimized TZB exposure and demonstrated potent activity in vitro against ESBL-phenotype isolates. We describe the pharmacodynamics of a WCK 4282 human-simulated regimen (HSR) in the neutropenic murine thigh model. METHODS: 19 clinical strains harboring ESBLs or CSase (EB; n=8 and PA; n=4) or serine-carbapenemases (EB; KPC n=4 or OXA-48-like n=3) were tested in vivo. Per CLSI, 19, 18, and 17 isolates were cefepime, ceftolozane/tazobactam, and piperacillin/tazobactam (TZP) non-susceptible, respectively. Thighs of neutropenic, female, CD-1 mice (3 per group) were inoculated with ~10(7) CFU/mL of bacterial suspension 2 h prior to dosing. Mice received WCK 4282 HSR, FEP HSR, or saline (controls) for 24 h. WCK 4282 HSR and FEP HSR provided plasma exposures in mice that were similar in f%T > MIC and fAUC to FEP-TZB 2 g-2 g and FEP 2 g, respectively, as IV infusions over 1.5 h q8h in humans. Bacterial densities and their changes at 24 h relative to 0 h controls were determined to assess efficacy and reported as mean±SD log(10) CFU/thigh. RESULTS: Bacterial burdens were 5.81±0.36 at 0 h and 9.29±0.88 at 24 h in untreated controls. WCK 4282 produced potent activity against ESBL/CSase producing EB and PA with WCK 4282 MIC ≤ 16 mg/L; mean change in log(10) CFU from 0 h was -1.70±0.77, while growth was observed with FEP alone. WCK 4282 produced variable activity against OXA-48-like harboring EB. Against KPC-harboring EB, WCK 4282 produced stasis to growth. Mean Log(10) CFU changes are reported in Table 1 and Figure 1. Table 1. Comparative efficacy of FEP HSR and WCK 4282 HSR by genotypic β-lactamase [Image: see text] Figure 1. Mean Change in log10CFU/thigh for 24 h controls, FEP HSR, and WCK 4282 HSR across the tested MIC distribution. [Image: see text] CONCLUSION: WCK 4282, a novel TZB containing regimen, resulted in enhance in vitro potency against ESBL/CSase and OXA-48-like producers. Humanized exposures of WCK 4282 produced substantial kill in vivo against ESBL/CSase producers with MICs ≤ 16 mg/L including FEP resistant/TZP non-susceptible PA. These data support further evaluations of WCK 4282 as a carbapenem-sparing regimen for ESBL/cephalosporinase harboring strains. DISCLOSURES: David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker’s Bureau)Wockhardt (Grant/Research Support)